Reading German for theological studies : a grammar and reader - Thompson, Carolyn Roberts, 1943- (Grand Rapids, MI. Baker Academic, 2021)
"Written to be used in a course or for self-study, this introductory German grammar shows students how to read and translate scholarly theological works"--
Includes bibliographical references (pages 243-245) and index.
Keywords: German language -- Readers -- Theology; German language -- Grammar; German language -- Textbooks for foreign speakers -- English